Analysis of investment risk management efficiency of Islami Bank Bangladesh Limited compared to conventional banks in Bangladesh - Mehjabin, Afia (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.